Energy-efficient and spectral-efficient mixed line rate optical WDM networks: a comparison. (24th April 2020) - Bajpai, Rochak; Iyer, Sridhar; Singh, Shree Prakash; Sengar, Sujata
The tremendous increase in volume and heterogeneity of traffic has resulted in significant innovations in telecommunication networks. In view of optical networks, by adopting a mixed line rate (MLR) strategy, wavelength division multiplexed networks can cost-effectively respond to diverse variety of traffic requirements which have heterogeneous service demands. From existing studies on MLR networks, it can be inferred that depending upon channel configuration, modulation format and link length, a spectral-efficient network can outperform a power-efficient network. In the current work, we compare the performance of a MLR network which is spectral-efficient and power-efficient. We conduct extensive simulations considering realistic parameters and physical layer impairments. To the network designers, our study advocates a MLR network which is spectrally efficient since; our results demonstrate that, in addition to achieving close packing of the channels, a spectrally-efficient MLR network is also able to achieve close performances to that shown by power-efficient MLR network.